Preface - Götz, Stefan; Süss-Stepancik, Evelyn (R&E-SOURCE, 2017)
This special issue is dedicated to the 13 th International Congress on Mathematical Education (ICME-13). This congress is held every four years. It is a worldwide meeting and a great opportunity to get in touch with various colleagues from countries all over the world. In 2016 ICME-13 took place in Hamburg (Germany) from 24 th of July to 31 st of July.